Analysis of Household Expenditure on Education in Cyprus - Andreou, Sofia N. (My University, 2012)
This paper investigates household expenditure on education in Cyprus and analyses factors affecting the level of education using data from the Family Expenditure Surveys 1996/7, 2002/3 and 2008/9. The results obtained show that the level of education expenditure increases with income across years. In addition, the proportion of households spending on private tutorials range between 60-90% at primary and secondary education levels, while the variation of this proportion over income groups is almost nonexistent. In empirical analysis the most profound factors affecting the level of household expenditure on education are income, number of children in household, region of residence and head‟s age and education. However, education and age of head appears to diminish over time. The findings can have implications for a wide range of issues regarding educational policies in Cyprus.
Keywords: Education expenditure; Cyprus; Household analysis